Botanical Survey of a Seminatural Saline Meadow - Tanyi, Péter; Nyakas, Antónia; K. Szabó, Zsuzsa; Pechmann, Ildikó (Acta Agraria Debreceniensis, 2006)
We made a botanical survey of a seminatural meadow situated in the vicinity of Hajdúnánás-Tedej in Hungary, using traditional phytocenological methods. The habitat, based on its soil-, and botanical characteristics, can be classified into the category of saline meadows. One of the landscape ecological values of this area is its mosaic-like structure and, as a consequence, this habitat can be divided into six characteristic associations with blurry borderlines and characteristic overlaps. Because of its rare plant species and species richness this area can be considered to be a valuable „seed bank” and a „stepping stone” in the ecological network among the larger, intensively cultivated fields. The area can be evaluated as moderately recovered, the natural species are dominant, but there are few disturbance tolerant species. Except for the two saline associations, the high grass associations, which make up about two-thirds of the habitat, are cut once a year; therefore, the agricultural utilisation of the area and its prevention against weediness are being assured at the same time.